The Effect Of Bingo Media To Improve Students Vocabulary Of The Eighth Grade Students At SMP S AL – Washliyah 27 Medan - Indah Eka Destry, Yulia Sari Harahap (Pusdikra Publishing, 2022)
There are some factors have influenced in teaching vocabulary. The creative teacher will use teaching method which appropriate with the students condition in the class and can attract them to be more interested in learning English especially vocabulary achievement. The aim of this research is to find the significance of Bingo Media in teaching English Vocabulary was observed and analyzed from students of eighth grade of SMP S Al – Washliyah 27 Medan. In this research, Bingo as media was implemented with discussion method in order was chosen in this research to solve the problem. The method of this research is quantitative by taking 60 students as the sample. The population of this research was all grade VIII students and the sample of this research were VIII – A as the experiment class, grade VIII – B as the control class. Instrument of the research was used multiple choice about Descriptive text. After the research gave the treatment by used Bingo in teaching Vocabulary it showed that pre-test average score of experimental group was 83,67 and control group was 69. Meanwhile, the post-test average of experimental groups was 59,33 and control group was 55. The research above the used Bingo and implementation of discussion method significantly affected on students vocabulary achievement. It could be concluded that the use of Bingo increasing students vocabulary achievement was affective. The result that found in this research was t observed was 6,94 and t table 2,00. It can state that there is significant difference between from students vocabulary scores taught by using Bingo and without Bingo. It means that Bingo Media are quite effective in improving students vocabulary achievement.